Regulation of Drug Disposition Gene Expression in Pregnant Mice with Car Receptor Activation - Bright, Amanda S. (Nucl Receptor Res, 2016)
More than half of pregnant women use prescription medications in order to maintain both maternal and fetal health. The constitutive androstane receptor (Car) critically affects the disposition of chemicals by regulating the transcription of genes encoding metabolic enzymes and transporters. However, the effects of Car activation on chemical disposition during pregnancy are unclear. This study aims to determine the degree to which pregnancy alters the expression of drug metabolizing enzymes and transporters in response to the pharmacological activation of Car. To test this, pregnant C57BL/6 mice were administered IP doses of vehicle, or a potent Car agonist, TCPOBOP, on gestation days 14, 15 and 16. Hepatic mRNA and protein expression of Car target genes (phase I, II and transporters) were quantified on gestation day 17. Pregnancy-related changes, such as induction of Cyp2b10, Ugt1a1 and Sult1a1 and repression of Ugt1a6, Gsta1, Gsta2 and Mrp6, were observed. Interestingly, the induction of Cyp2b10, Gsta1, Gsta2 and Mrp2-4 mRNAs by TCPOBOP was attenuated in maternal livers suggesting that Car activation is impeded by the biochemical and/or physiological changes that occur during gestation. Taken together, these findings suggest that pregnancy and pharmacological activation of Car can differentially regulate the expression of drug metabolism and transport genes.